Validation of a wearable system for 3D ambulatory L5/S1 moment assessment during manual lifting using instrumented shoes and an inertial sensor suit. (26th March 2020) - Faber, G.S.; Kingma, I.; Chang, C.C.; Dennerlein, J.T.; van Dieën, J.H.
Abstract: This study aimed to evaluate the accuracy of 3D L5/S1 moment estimates from an ambulatory measurement system consisting of a wearable inertial motion capture system (IMC) and instrumented force shoes (FSs), during manual lifting. Reference L5/S1 moments were calculated using an inverse dynamics bottom-up laboratory model ( bu LABmodel ), based on data from a measurement system comprising optical motion capture (OMC) and force plates (FPs). System performance of (1) a bottom-up ambulatory model ( bu AMBmodel ) using lower-body kinematic IMC and FS data, and (2) a top-down ambulatory model ( td AMBmodel ) using upper-body kinematic IMC data and hand forces (HFs) were compared. HFs were estimated using full-body kinematic IMC data and FS forces. Eight males and eight females lifted a 10-kg box from different initial vertical/horizontal positions using either a free or an asymmetric lifting style. As a measure of system performance, root-mean-square (RMS) errors were calculated between the reference ( bu LABmodel ) and ambulatory ( td AMBmodel & bu AMBmodel ) moments. The results showed two times smaller errors for the td AMBmodel (averaged RMS errors < 20 Nm or 10% of peak extension moment) than for the bu AMBmodel (average RMS errors < 40 Nm or 20% of peak extension moment). In conclusion, for ambulatory L5/S1 moment assessment with an IMC + FS system, using a top-down inverse dynamics approach with estimated hand forces is to be preferred over a bottom-up approach.